2021
DOI: 10.1002/alz.12373
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐amyloid pore linked to controlled calcium influx into the cell: A new paradigm for Alzheimer's Disease

Abstract: Despite tremendous worldwide efforts, clinical trials assessing Alzheimer's disease (AD)‐related therapeutics have been relentlessly unsuccessful. Hence, there is an urgent need to challenge old hypotheses with novel paradigms. An emerging concept is that the amyloid‐beta (Aβ) peptide, which was until recently deemed a major player in the cause of AD, may instead modulate synaptic plasticity and protect against excitotoxicity. The link between Aβ‐mediated synaptic plasticity and Aβ trafficking is central for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The β-barrel aggregates first observed in an 11-residue peptide derived from the slow-aggregating αB crystalline form have been proposed as toxic oligomers of amyloid aggregation 55 due to their well-defined structures and compatibility to the “amyloid-pore” 56 hypothesis of amyloid toxicity. 44,50 The formation of β-barrel oligomers by full-length Aβ peptides was supported by hydrogen exchange mass spectrometry, NMR measurement, cryo-EM essays, and computational simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-barrel aggregates first observed in an 11-residue peptide derived from the slow-aggregating αB crystalline form have been proposed as toxic oligomers of amyloid aggregation 55 due to their well-defined structures and compatibility to the “amyloid-pore” 56 hypothesis of amyloid toxicity. 44,50 The formation of β-barrel oligomers by full-length Aβ peptides was supported by hydrogen exchange mass spectrometry, NMR measurement, cryo-EM essays, and computational simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, hIAPP and hIAPP(S20G) could form β-barrel formations, which were proposed as toxic oligomers of amyloid aggregation. 6,49–52,55,56 The β-barrel propensity of hIAPP(S20G) was three times larger than that of hIAPP. Another recent experimental study using transmission electron microscopy (TEM) imaging also demonstrated that the barrel-like oligomers of hIAPP(S20G) were more abundant than hIAPP wild-type.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous basic and clinical studies have demonstrated the direct role of synapse in cognitive impairment. At the biological level, the synaptic function is distorted in the settings of neurogenerative diseases, especially the ‘synaptic plasticity’ in AD [ 25 ]. Synaptic plasticity is closely associated with the formation of learning and memory [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…aggregation, and pore formation (see Table 1). Together, these would trigger initial events [e.g., mitochondrial dysfunction with calcium influx (Pannuzzo, 2022), oxidative stress] followed by somewhat downstream endosomal/lysosomal dysfunction (Lee et al, 2022) again to more mitochondrial ROS and systemic inflammation). However, a counter-argument to such a hypothesis is that no protein aggregates, or amyloid fibrils, have been detected in EPM1 patient cells, whether from neurons or glia, or animal models.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%